Ճապոնիայի տնտեսական քաղաքականությունը Հայաստանում (1992-2021 թթ.) - Yeva Harutyunyan (Banber Arevelagitut'yan Instituti)
The purpose of this article is to show the economic policy of Japan towards Armenia after the establishment of Armenian-Japanese diplomatic relations. The article presents three phases of Japan's economic policy, taking into account the type of assistance provided by Japan to Armenia, which is correlated with Armenia's economic and GDP’s growth. The first phase covers 1992-99, during which bilateral economic relations were limited to grant assistance provided by Japan to Armenia, with the aim of supporting the economic recovery of the newly independent state and ensuring sustainable economic growth. The second phase (2000-04) marked the beginning of economic cooperation between the two countries. Due to its stable economic growth, Armenia received loans from Japan for developing economic infrastructures.